2012
DOI: 10.1080/10549811.2012.706533
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Vegetable Rennet (Withania coagulans[Stocks] Dunal)—A Critically Endangered Medicinal Plant

Abstract: Withania coagulans (Stocks) Dunal (Solanaceae), popularly called vegetable rennet, is a critically endangered and highly valued medicinal plant. Overexploitation and reproductive failure forced the plant species toward the verge of complete extinction. We describe here the development of a simple, rapid, and cost effective in vitro micropropagation system for W. coagulans for mass-scale production of true-to-type plantlets using nodal shoot segments. Exactly 95.5 ± 0.34% explants responded within 8-10 days (d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Poly-gamo-dioecious nature of flowers and self-incompatibility (Gilani et al, 2009) limits the chances of seed setting and the plant species is found in vegetative state under arid conditions (Bhandari, 1990). The natural regeneration rate does not sustain to keep up with the exploitation rate and the plant species is threatened in its habitat and declared critically endangered (Jain et al, 2010;Rathore et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Poly-gamo-dioecious nature of flowers and self-incompatibility (Gilani et al, 2009) limits the chances of seed setting and the plant species is found in vegetative state under arid conditions (Bhandari, 1990). The natural regeneration rate does not sustain to keep up with the exploitation rate and the plant species is threatened in its habitat and declared critically endangered (Jain et al, 2010;Rathore et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…A number of tissue culture studies have been carried out on W. somnifera, but W. coagulans received little attention so far for biotechnological studies (Mirjalili et al, 2011;Mishra et al, 2012;Kushwaha et al, 2013;Rathore and Kheni, 2015). A few attempts were made on in vitro propagation of W. coagulans using different explants and mode of regeneration (Jain et al, 2009(Jain et al, , 2010Valizadeh, 2009, 2011;Rathore et al, 2012). Plant regeneration techniques are attractive and potential ways for utilization of plant genetic resources as well as their conservation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Withania coagulans (Stocks) Dunal, a shrub from Solanacea family, locally known as local inhabitants [5,6]. The berries from this plant due to the presence of enzyme in husk and pulp are used as milk coagulating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation studies on W. cogulans is reviewed recently (Teixeira da Silva et al 2015). Its natural propagation occurs through seeds, which is a slow process and resultant seeds may not germinate in the absence of favourable germination conditions (Rathore et al 2012). …”
Section: Introductionmentioning
confidence: 99%